Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the probability [tex]\( P(B) \)[/tex], we can use the formula for the probability of the union of two events:
[tex]\[ P(A \text{ OR } B) = P(A) + P(B) - P(A \text{ AND } B) \][/tex]
We are given the following probabilities:
- [tex]\( P(A) = 0.3 \)[/tex]
- [tex]\( P(A \text{ OR } B) = 0.63 \)[/tex]
- [tex]\( P(A \text{ AND } B) = 0.17 \)[/tex]
We need to isolate [tex]\( P(B) \)[/tex] in the formula. We can rearrange the formula to solve for [tex]\( P(B) \)[/tex]:
[tex]\[ P(A \text{ OR } B) = P(A) + P(B) - P(A \text{ AND } B) \][/tex]
Rearranging to solve for [tex]\( P(B) \)[/tex]:
[tex]\[ P(B) = P(A \text{ OR } B) - P(A) + P(A \text{ AND } B) \][/tex]
By substituting the known values into the equation:
[tex]\[ P(B) = 0.63 - 0.3 + 0.17 \][/tex]
Performing the arithmetic operations step-by-step:
[tex]\[ P(B) = 0.63 - 0.3 = 0.33 \][/tex]
[tex]\[ P(B) = 0.33 + 0.17 = 0.5 \][/tex]
Therefore, the probability [tex]\( P(B) \)[/tex] is:
[tex]\[ P(B) = 0.5 \][/tex]
[tex]\[ P(A \text{ OR } B) = P(A) + P(B) - P(A \text{ AND } B) \][/tex]
We are given the following probabilities:
- [tex]\( P(A) = 0.3 \)[/tex]
- [tex]\( P(A \text{ OR } B) = 0.63 \)[/tex]
- [tex]\( P(A \text{ AND } B) = 0.17 \)[/tex]
We need to isolate [tex]\( P(B) \)[/tex] in the formula. We can rearrange the formula to solve for [tex]\( P(B) \)[/tex]:
[tex]\[ P(A \text{ OR } B) = P(A) + P(B) - P(A \text{ AND } B) \][/tex]
Rearranging to solve for [tex]\( P(B) \)[/tex]:
[tex]\[ P(B) = P(A \text{ OR } B) - P(A) + P(A \text{ AND } B) \][/tex]
By substituting the known values into the equation:
[tex]\[ P(B) = 0.63 - 0.3 + 0.17 \][/tex]
Performing the arithmetic operations step-by-step:
[tex]\[ P(B) = 0.63 - 0.3 = 0.33 \][/tex]
[tex]\[ P(B) = 0.33 + 0.17 = 0.5 \][/tex]
Therefore, the probability [tex]\( P(B) \)[/tex] is:
[tex]\[ P(B) = 0.5 \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.